KAJIAN TERHADAP PERKEMBANGAN SEKOLAH MUHAMMADIYAH - Leny Marlina (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
Muhammadiyah was established by K.H. Ahmad Dahlan and his friends on the18th of November 1912 (8 Dhual-Hijjah 1330 H) as a means to deepen knowledge and understanding of Religious science for membersof the organization which was formed to teach and spread the teachings of Islam by Muslims themselves. There are five roles of Muhammadyah. They are tajdid, one of the components of the nation, citizens of the IslamicWorld, and Muhammadiyah is responsible for the realization of theprogress of Muslims in all spheres of life, free from marginalization,alienation, and salvation in the constellation and global civilization. As acitizen of the world, Muhammadiyah is always responsible for the creationof a just world order, prosperous and high civilized accordance with themission to bring the message of Islam as rahmatan lil alamin. The fiveroles serve as the basis for the organization in designing, shaping, andimplementing several programs of this organization.